Experimental and Numerical Analysis of Heat Transfer in a Tall Vertical Concentric Annular Thermo-siphon at Constant Heat Flux Condition. Issue 11 (3rd July 2019) - Mustafa, Jawed; Siddiqui, Mohammad Altamush; Anwer, Sayed Fahad
ABSTRACT: The present work deals with the numerical and experimental analyses to study the detailed behavior of the thermally induced flow of water in an open vertical annulus, circulating through a cold leg forming a closed loop thermo-siphon. Spatio-temporal behavior of fluid flow is also studied for variety of heat fluxes. The annuli in the present study have a radius ratio of 1.184 and aspect ratio (length to annular gap) equal to 352. The objective of the present work is to quantify the effect of heating on design parameters such as liquid and wall temperatures, mass flow rate, and heat transfer coefficient. Experiments have also been conducted on a similar system with water at constant heat flux of 1 kW/m 2, 2.5 kW/m 2, 5 kW/m 2, 7.5 kW/m 2, 10 kW/m 2, 12.5 kW/m 2 and 15 kW/m 2 . For numerical purpose, a two-dimentional solver has been developed for direct numerical simulation of the essential thermally induced flow dynamics The numerical solution was thus performed for Rayleigh numbers ranging between, 4.4 × 10 3 and 6.61 × 10 4 which correspond to the given heat flux, respectively.